2018
DOI: 10.1016/j.envpol.2018.07.126
|View full text |Cite
|
Sign up to set email alerts
|

Particulate emission from the gasification and pyrolysis of biomass: Concentration, size distributions, respiratory deposition-based control measure evaluation

Abstract: Gasification and pyrolysis technologies have been widely employed to produce fuels and chemicals from solid wastes. Rare studies have been conducted to compare the particulate emissions from gasification and pyrolysis, and relevant inhalation exposure assessment is still lacking. In this work, we characterized the particles emitted from the gasification and pyrolysis experiments under different temperatures (500, 600, and 700 °C). The collection efficiencies of existing cyclones were compared based on particle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…This study first explored the size distribution of 6-PPDQ in inhalable coarse particles. The respiration deposition efficiency of particles and induced health effects are partially dependent on particle size, such as that of halogenated flame retardants. ,, On the basis of the sampler design principles, , the 0–2 (4.7–10 μm), 3–5 (1.1–4.7 μm), and 6–7 (0.43–1.1 μm) impactor stages roughly represented the corresponding deposition regions of the head airways (HA), tracheobronchial (TB), and pulmonary alveoli (PA) areas in the human respirational system. Collectively, approximately 62%–71% of the target 6-PPDQ was predominantly deposited in the HA area, and a lower proportion than that, of 15%–23% and 11%–14%, was observed in the TB and PA areas, respectively (Table S4).…”
Section: Resultsmentioning
confidence: 99%
“…This study first explored the size distribution of 6-PPDQ in inhalable coarse particles. The respiration deposition efficiency of particles and induced health effects are partially dependent on particle size, such as that of halogenated flame retardants. ,, On the basis of the sampler design principles, , the 0–2 (4.7–10 μm), 3–5 (1.1–4.7 μm), and 6–7 (0.43–1.1 μm) impactor stages roughly represented the corresponding deposition regions of the head airways (HA), tracheobronchial (TB), and pulmonary alveoli (PA) areas in the human respirational system. Collectively, approximately 62%–71% of the target 6-PPDQ was predominantly deposited in the HA area, and a lower proportion than that, of 15%–23% and 11%–14%, was observed in the TB and PA areas, respectively (Table S4).…”
Section: Resultsmentioning
confidence: 99%
“…Environmental performance includes emissions like carbon dioxide during the combustion reactions and passage across the bed without conversion to carbon monoxide. Methane emissions are possible during the storage of waste before gasification [36]. Normally, fixed-bed gasifiers have acceptability to higher sizes of feedstock compared with fluidized bed gasifiers.…”
Section: Attribute Valuesmentioning
confidence: 99%
“…Meanwhile, it was also demonstrated that CFD modelling could achieve more detailed and accurate results as it incorporates the factors of reactor design, fluid mechanics, mass and heat transfer, etc [125,126]. Highly accurate simulations become necessary and useful for predicting product composition and optimal process condition [127][128][129], as well as providing the basis for downstream techniques such as techno-economic analysis (TEA) [130,131] and life-cycle assessment (LCA) [132,133].…”
Section: Cfd Modelsmentioning
confidence: 99%